Equity and accessibility in health? Out-of-pocket expenditures on health care in middle income countries: evidence from Mexico - Armando Arredondo; Patricia Nájera
This study analyzes the results of a cross-sectional survey which set out to determine the costs to patients of searching for and receiving health care in public and private institutions. The information analyzed was obtained from the study population of the Mexican National Health Survey. The dependent variable was the out-of-pocket users' costs and the independent variables were the insurance conditions, type of institution and income. The empirical findings suggest that there is a need for a more detailed analysis of user costs in middle income countries in general, where the health system is based on social security, public assistance and private institutions. This study shows that the out of pocket costs faced by users are inequitable and fall disproportionately upon socially and economically marginalized populations.